FRI0040 GENDER DISCREPANCY IN RHEUMATOID ARTHRITIS: PATIENTS' AND PHYSICIANS' PERSPECTIVE. (June 2019) - Duca, Ilaria; Spinelli, Francesca; Altobelli, Alessio; Lucchino, Bruno; Gioia, Chiara; Pirone, Carmelo; Valesini, Guido; Conti, Fabrizio; Franco, Manuela DI
Abstract : Background: Rheumatoid Arthritis (RA) is more prevalent among female individuals. Sex and gender differences may influence disease's progression and prognosis. To date, the influence of physicians' gender in the evaluation of RA activity is still largely unknown. Objectives: aim of the study was to investigate a possible discrepancy in the assessment of disease activity in RA patients evaluated by male and female physicians. Further aim was to compare patient and evaluator perceptions about disease activity and global health status. Methods: we enrolled consecutive RA patients. Each patient was separately visited by a female and a male rheumatologist of the same age and training level. Tender (TJ) and swollen joints (SJ) count was performed. Global Health (GH), physician's (E-VAS) and patient's (P-VAS) disease activity were reported using a visual analogue scale (VAS 0-100). Both examiners were blinded on ESR and CRP. A third rheumatologist assessed disease activity by DAS28-ESR, CDAI and SDAI. Results: we enrolled 154 patients (122 F, 32 M). GH and P-VAS were significantly higher when collected by the female examiner compared to the male one (respectively, 41, 1 ± 24, 4 vs 36, 1 ± 24, 3, p<0, 0001 and 41, 7 ± 26, 2 vs 35, 3 ± 25, 4; p<0, 0001; figure 1 ), as well as DAS28-ESR values (3, 19 ± 1, 5 vs 2, 97 ± 1, 5; p<0, 0001; figure 2 ) but not CDAI and SDAI. On the contrary, male E-VAS was significantly higher compared to female one (26, 8 ± 27 vs 20, 5 ± 20, 8; p<0, 0001; figure 1 ). GH, P-VAS and DAS28 significantly differ when the analysis was restricted to female patients (p<0, 0001); among male patients, only P-VAS was significantly higher when collected by the female examiner (36, 5 ± 24, 7 vs 30, 4 ± 25, 4; p<0, 0001). According to the DAS28-ESR cut off, 39, 6% of patients were in remission when evaluated by the female examiner compared to 42, 9% when examined by the male physician; the probability of being judged as having an active disease was not different between the female and the male examiner (p=ns). Overall, the agreement between the female and male evaluation of disease activity was high [Intraclass correlation coefficient (ICC-K) 0, 92 for GH; 0, 81 for E-VAS; 0, 89 for P-VAS; 0, 95 for DAS28-ESR; p<0, 0001]. When comparing patient and examiner perception of the disease activity, P-VAS values were significantly higher than E-VAS in both female and male examiners (41, 7 ± 26, 2 vs 20, 5 ± 20, 8; 35, 3 ± 25, 4 vs 26, 8 ± 27, 1; p<0, 0001; figure 3 ).The general agreement between male and female examiner and the whole patient population was moderate (K 0, 65 and 0, 62, respectively; p<0, 0001), with the lowest agreement between female patients and male examiner (K 0, 58; p<0, 0001). Female physician had an higher agreement with both male and female patients (K 0, 78, K 0, 62 respectively; p<0, 0001). Conclusion: subjective measure of global health status and disease activity (GH, P-VAS) are generally higher when collected by a female examiner compared to a male one, especially among female patients. This gender discrepancy in subjective measures could influence the evaluation of disease activity indices; however, this does not affect the probability of being defined in remission. Overall, patients have a higher perception of disease activity compared to the health care providers, and the agreement between physician and patients is only moderate, with female patients having the worst perception. Female physician tend to be more in agreement with the patients' judgement of disease activity maybe because of a more emphatic setting established by the female health care provider. Disclosure of Interests: None declared